2003
DOI: 10.1007/s00436-002-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three antigen detection tests for diagnosis and follow-up of falciparum malaria in travellers returning to Berlin, Germany

Abstract: We determined the sensitivity and specificity of three rapid immunochromatographic malarial antigen detection test systems (RDTs) for the detection of Plasmodium falciparum and assessed the quality of follow-up results. ParaSight-F and ICT Malaria detect histidinerich protein-2 (HRP-2), whereas OptiMal detects plasmodial lactate dehydrogenase (pLDH). ParaSight-F performed with 95.1% sensitivity and 97.1% specificity (554 patients tested of whom 144 had falciparum malaria). ICT Malaria performed with 95.7% sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…Using these reading times, the performance of the VIKIA Malaria Ag Pf/Pan™ test was similar to those of the CareStart Malaria™ test or those found in previous studies [21-26]. …”
Section: Discussionsupporting
confidence: 81%
“…Using these reading times, the performance of the VIKIA Malaria Ag Pf/Pan™ test was similar to those of the CareStart Malaria™ test or those found in previous studies [21-26]. …”
Section: Discussionsupporting
confidence: 81%
“…The sensitivity is comparable with an earlier study by Bharti et al [23] on First Response Malaria (sensitivity: 93%). On the other hand the sensitivity for ICT Malaria Combo was found to be lower (90.83%; 95% CI: 86.83–94.83) than the reported value of 95.7% by Grobusch et al [9] (Table 2). …”
Section: Discussioncontrasting
confidence: 62%
“…Most studies enrolled a consecutive or random sample of eligible patients, but in one study the procedure of patient enrollment was not clearly described [20]. Three studies were considered to be inappropriate because the studies excluded severe or special patients (such as pregnant women) from the studies [2022]. Seven studies did not supply sufficient information about the blindness of index or reference standard tests [4, 68, 16, 22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies did not supply sufficient information about the blindness of index or reference standard tests [4, 68, 16, 22, 23]. Four studies reported that the tests were not performed or the results were missed in a portion of the patients [14, 20, 24, 25]. According to the criteria of the evaluation, 75% of studies had a low risk of bias in the patient selection domain, 50% of studies were judged to have low risk in the other 3 domains, and only 1 study was assessed to be at high risk of bias in patient selection and flow and timing domains [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation